Ict, sts approach and education: a beneficial adhesion - Júlia Bômfim Rodrigues (Temas em Educação e Saúde, 2019)
Regarding the modernization of society and the emergence of new technologies, this article discusses the use of approaches such as STS and ICT that become increasingly common in education, which makes us wonder if they are methodologies beneficial or harmful, it is sought to comment on what these approaches deal with and to refer to an article about a school experience.